Social movement organizations in Spain: Being partial as the prefigurative enactment of social change. Issue 4 (13th November 2017) - Simsa, Ruth; Totter, Marion
Abstract : Purpose: The purpose of this paper is to analyze how activists of the Spanish protest movement 15M conceptualize organizational practices in relation to the movement's goals. Design/methodology/approach: In order to theoretically understand social movement organizations (SMO), the concept of partial organization is placed within the context of the politics of prefiguration. Empirically, the paper is based on field research conducted in Spain in three consecutive years (2014-2016) that included 82 qualitative interviews and participant observation. Findings: Activists consider the organizational practices as crucial means to achieve social change. They conceptualize SMO in a meaningful and systematic way as partial organizations, specifically, by aiming at open membership and non-hierarchical structures. As they do this to enact the movement's goals prefiguratively in their daily organizational practices, the limits and restrictions of the practices of self-organization are widely accepted. Research limitations/implications: The research focused on studying the relatively young and often very successful organizations of the Spanish movement. It remains open to what extent the prefigurative practices will survive organizational life cycles. Practical implications: By contributing to a deeper understanding of the underlying philosophy of SMO, this paper is useful for social movement activists and scholars. Originality/value: This is one of the first papers, which analyzes the organizations of the Spanish protest movement with respect to both empirical and theoretical aspects.